Organizational ambidexterity in higher education institutions: proposition of evolutive stages of ambidexterity - Soares, Juliano Lima; Reis, Dálcio Roberto dos (Revista de Administração da UFSM, 2021)
Purpose – The general objective of the research was to propose evolutionary stages of organizational ambidexterity. Design/methodology/approach – The research methodology was classified as an exploratory and descriptive study, whose method of data collection was through a questionnaire, the sample was census by adherence, from a population of 110 higher education institutions (HEI), participating in the study 79 cases, distributed throughout the Brazilian territory. Findings – It is noteworthy that HEI are part of the same economic group, and even though 96% of the cases were classified as ambidextrous organizations, there was a great dispersion between them, suggesting some heterogeneity of the investigated cases. Originality – With the findings, the proposition of the existence of different levels of ambidexterity arose. This phenomenon, in a preliminary way, was labeled as the Degree of Maturity of Ambidextrous Organizational